Hesperidin Nanoformulation: A Potential Strategy for Reducing Doxorubicin-Induced Renal Damage via the Sirt-1/HIF1-α/VEGF/NF-κB Signaling Cascade - Fatemah A. Alherz; Thanaa A. El-Masry; Ghaleb A. Oriquat; Engy Elekhnawy; Nora Hamad Al-Shaalan; Mohamed M. S. Gaballa; Enas I. El Zahaby; Maysa M. F. El-Nagar (MDPI AG, 2024)
Hesperidin (Hes) functions as a strong antioxidant and anti-inflammatory to guard against damage to the heart, liver, and kidneys. Nevertheless, due to its restricted solubility and bioavailability, a delivery method is required for it to reach a specific organ. In this study, ion gelation was used to synthesize a chitosan/hesperidin nanoformulation. Numerous characterization techniques, such as zeta potential, particle size, XRD, TEM, SEM, and FTIR analyses, were used to corroborate the synthesis of hesperidin nanoparticles (Hes-NPs). Male albino mice were given a pretreatment dose of 100 mg/kg, PO, of Hes or Hes-NPs, which was administered daily for 14 days before the induction of doxorubicin nephrotoxicity on the 12th day. Kidney function (urea and creatinine levels) was measured. Lipid peroxidation (MDA) and antioxidant enzyme (CAT and SOD) activities were estimated. TNF-α, IL-1β, and VEGF content; histopathological examination of kidney tissue; and immunohistochemical staining of NF-κB, Caspase-3, BAX, Bcl-2, and TGF-β1 were evaluated. The gene expressions of Sirt-1, Bcl-2, VEGF, HIF1-α, and Kim-1 were also considered. The results showed that pretreatment with Hes or Hes-NPs reduced doxorubicin's nephrotoxic effects, with Hes-NPs showing the greatest reduction. Kidney enzyme and MDA content were lowered in response to the Hes or Hes-NP pretreatment, whereas antioxidant enzyme activities were increased. Hes or Hes-NP pretreatment suppressed the levels of TNF-α, IL-1β, VEGF, NF-κB, Caspase-3, BAX, and TGF-β1; however, pretreatment increased Bcl-2 protein levels. Furthermore, the gene expressions of Sirt-1, Bcl-2, VEGF, HIF1-α, and Kim-1 were considerably higher with Hes-NP than with Hes treatment. These results suggest that Hes-NP treatment might reduce DOX-induced nephrotoxicity in mice via modulating Sirt-1/HIF1-α/VEGF/NF-κB signaling to provide antioxidant, anti-inflammatory, and anti-apoptotic effects.